New Trends in the Use of Metaphors and Similes Including Names of Food in Modern Russian Prose - Nikolina, Natalia; Petrova, Zoya (Slavica, 2021)
The article discusses metaphors and similes including culinary vocabulary, functioning in modern Russian prose. The purpose of the article is to identify new trends in the use of such figurative constructions in modern prose compared with the previous period in the development of Russian literature. The work outlines the main thematic groups of names of food and drinks used in prosaic texts, and notes changes in their composition and character. New elements in the semantic classes of «vehicles» of metaphors and similes are also revealed. A tendency towards the differentiation and concretization of images of comparison, which is characteristic of modern prose, is noted, and the means of its implementation (specific names and qualifying definitives) are described. The article considers new subjects of comparison and figurative parallels used in modern prose texts.